2021
DOI: 10.1037/sah0000344
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of weight status on pediatric decision-making and medical student awareness of its influence.

Abstract: The objective was to investigate the influence of pediatric patient and mother weight status on assessment/ treatment decisions of medical students, as well as student reaction to feedback about differential weightbased decision-making. Medical students (n = 120) viewed vignette scenes of a static virtual human pediatric patient presenting to a physician with back pain, accompanied by her mother. Cues of patient and mother weight (healthy, obesity) were manipulated across scenes. Participants provided ratings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…This correlation suggests that delays in care for SCFE PLOS ONE patients may be more complex than previous research has indicated. Current healthcare providers acknowledge that unfavorable views toward obese patients exist, and multiple metareview studies have indicated these negative perceptions have persisted for many decades in the healthcare field [67][68][69][70][71]. Obese patients have reported feeling dismissed by their healthcare provider regarding pain concerns [67,71,72].…”
Section: Plos Onementioning
confidence: 99%
“…This correlation suggests that delays in care for SCFE PLOS ONE patients may be more complex than previous research has indicated. Current healthcare providers acknowledge that unfavorable views toward obese patients exist, and multiple metareview studies have indicated these negative perceptions have persisted for many decades in the healthcare field [67][68][69][70][71]. Obese patients have reported feeling dismissed by their healthcare provider regarding pain concerns [67,71,72].…”
Section: Plos Onementioning
confidence: 99%